PENGARUH PERUSAHAAN KELUARGA DAN PERAN KOMISARIS INDEPENDEN TERHADAP PRAKTIK MANAJEMEN LABA DI INDONESIA - Go Meliana Indah Lestari; Senny Harindahyani (Akuntansi dan Teknologi Informasi, 2017)
Family firms don’t have effective oversight, therefore they tend to do earnings management higher compare than others. This study aims to prove whether this phenomenon true or not and whether the role of independent commissioners have been effectively overcome the problem. Data used in this research covers all firms listed in Indonesian Stock Exchange for the period of 2012 to 2014, except for banking and finance sector. The study is conducted using multiple linear regressions. The result shows that there is no significant different between family firms and non-family firms to manage earnings, and the role of independent directors can’t decrease the earnings management in family firms.